Organogelator based on long alkyl chain attached excimer precursor: Two channels of TICT, highly efficient and switchable luminescence. (September 2020) - Ouyang, Mi; Zhuo, Chaozheng; Cao, Feng; Pan, Guoxiang; Lv, Chunyan; Yang, Shengchen; Li, Chengjian; Zhang, Cheng; Sun, Jingwei; Zhang, Yujian
Abstract: A low molecular mass organic gelator (LMOG) T16 was obtained by introducing a long alkyl chain into an excimer precursor α–CN–TPA. Immobile organogels of T16 exhibiting both thermochromic and mechanochromic fluorescence switching between blue and green could be formed. Far more than expected, the long alkyl chain endows T16 with unique two channels of twisted intramolecular charge transfer (TICT) emission in solution and highly luminescent properties in both a gel and solid state (crystal). The fluorescence distribution ratio of the two channels is dependent on irradiation wavelength and solvent polarity, leading to distinct effects of aggregation induced enhanced emission (AIEE) and gelation induced enhanced emission (GIEE), respectively. The fluorescent quantum efficiency of T16 is increased more than 380 times in xerogel and almost 500 times in the crystal compared with that of α–CN–TPA crystal, though both molecules have the same conjugated unit. The radiant transition is found to be transformed from a forbidden state in α–CN–TPA to the allowed state in T16, owing to the incorporation of a long alkyl chain which influences the self-assembly structure and intermolecular interactions. Antiparallel molecular H-stacking and multi-layered self-assembly are constructed in T16 under the driving force of π−π, electrostatic and long alkyl-alkyl chain interactions. These findings offer a simple and interesting platform for manipulating the fluorescence radiation characteristics. Graphical abstract: Image 1 Highlights: A low molecular mass organic gelator with switchable luminescence was synthesized. The gelator exhibits two channels of twisted intramolecular charge transfer emission. The radiant transition is found to be transformed from a forbidden state to the allowed one. Introducing a long alkyl chain into an excimer precursor is a strategy to develop highly luminescent organogelators.